Interaksi Sosial Nabi Muhammad Saw dan Komunitas Yahudi: Telaah Hadis dalam Perspektif Historis-Psikologis - Budiman, Arif; A’yun, Qurrota (Universitas Islam Negeri Alauddin, 2024)
This article aims to examine the relationship between the Prophet Muhammad and the Jewish community in Medina based on traditions, primarily from the book of Ṣaḥīḥ al-Bukhārī. The research focuses on the social interactions, both positive and negative, as well as the political, social and religious factors that influenced this relationship. Using a qualitative research design through analysis of hadith texts and Islamic historical literature, historical and psychological approaches were taken to analyze these interactions. This research resulted in the following findings: First, in general, it is found that there is a historical fact that there is a form of cooperation and respect between the Prophet and the Jews in two crucial cases, namely satire literature and the case of killing a Jewish person so that there is tension. Second, from the psychological context, the factor that causes conflict and confrontation is the factor of cultural inheritance (transferred culture) is a significant factor in influencing the Prophet's relationship with the Jewish community. The negative disposition that has been rooted is proven to erupt various acts of treason in various forms.